English Speaking Problems in Covid-19 Pandemic at Second Grade of Vocational High School - Efa Silfia; Ridho Praja Dinata (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The aim of this research was to find out students’ problems faced in speaking English during the covid-19 pandemic and the solutions to overcome these problems. The researcher used qualitative research. The researcher took six students of class XI Accounting 1 as research subjects. In this research, researchers used interview sheets and interviewed students to collect data. Based on the results of the study, regarding the problems of students in learning to speak at Vocational High School 2 Jambi City, there were several student problems during the pandemic, located in the sixth question about the difficulty of speaking English, namely, lack of confidence, embarrassed to speak English, online learning made students feel less confident, self-confident in learning time in class, so that the problems faced by students were lack of pronunciation, fear of making mistakes when speaking English, lack of motivation of students in speaking English, students got into trouble because it was based on problems experienced and experienced by themselves. In learning to speak English, based on interviews, there were solutions to the problem, such as, using more English, translating sentences on Google, by listening to English music.